Therapeutic efficacy of pirfenidone and nintedanib in pulmonary fibrosis; a systematic review and meta-analysis - Yiting Qiu; Wei Ye (Annals of Thoracic Medicine)
This updated systematic review and meta-analysis pooled the results of previous clinical trials assessing the effects of pirfenidone and nintedanib on patients with pulmonary fibrosis. Scopus, the Cochrane Library, PubMed, and Web of Science were searched from the inception to April 12, 2025, to identify randomized controlled trials measuring the effect of pirfenidone and nintedanib on pulmonary fibrosis. Because of high methodological heterogeneity, we utilized a random-effects model (DerSimonian-Laird) to perform this meta-analysis. Finally, 18 articles with 20 randomized controlled trials were included in this meta-analysis. We found that compared to placebo, treatment with the two antifibrotic drugs increased forced vital capacity (FVC) predicted (weighted mean difference [WMD] 3.12%, 95% confidence interval [CI] [1.41, 4.82], I2 = 53.30%), FVC volume (WMD 87.44 ml, 95% CI [59.32, 115.57], I2 = 99.4%), and the distance walked in the 6-minute walk test (WMD 24.63 m, 95% CI [16.05, 33.22], I2 = 0.00%). However, compared to placebo, treatment with the two antifibrotic drugs did not significantly change the diffusing capacity of the lungs for carbon monoxide (WMD 1.38 ml/min/mmHg, 95% CI [−9.42, 12.18], I2 = 0.00%). Therapeutic benefits were observed for both pirfenidone and nintedanib and for both idiopathic pulmonary fibrosis (IPF) and non-IPF. Pirfenidone and nintedanib can improve lung function and functional capacity in patients with different types of pulmonary fibrosis.